PEMODELAN STATE SPACE MOTOR INDUKSI TIGA FASA SEBAGAI PENGGERAK MOBIL LISTRIK - Angga Wahyu Aditya; Ihsan Ihsan; Restu Mukti Utomo; Hilmansyah Hilmansyah (Jurnal Teknologi, 2020)
The use of induction motors in electric cars was developed since vector control technology was discovered and developed. In vector control technology requires dynamic modeling of induction motors on electrical and mechanical sides. Along with the development of controlling system technology, especially controllers based on system modeling, dynamic modeling of induction motors that are simple and easy to process to design a controller is needed. The state space equation is a solution that can be used to simplify induction motor modeling so that it is easier to determine vector control equations and design controllers to get maximum induction motor performance. In addition, the induction motor state space equation can also be used to design and determine the stability of an induction motor control system. The response to the basic characteristics of an induction motor includes the response of the characteristics of the stator current, rotor speed and electromagnetic torque at no-load conditions and at full load.